Estudos para especificação e modelagem de estruturas e organização de um dicionário monolíngue de Libras - Martins, Tânia Aparecida (2020)
Despite publications in the field of lexicographic studies of sign languages, there are still many demands for solutions and resources to meet the needs of people with deafness, especially with regard to composition, formatting and access to lexical items recorded in dictionaries. of those languages. This thesis discusses and presents a dictionary proposal specifically focused on Libras, that is, monolingual, a resource that has long been demanded not only by the Brazilian deaf community, but also by educators and language scholars. With this objective in mind, the main questions that guided this research were: (i) How should Libras dictionaries, typically monolingual, be structured? Or more precisely, based on their internal structures, how should the macro and microstructural axes of this type of dictionary be organized? And, also (ii) with regard to the composition not only of the search keys, but also of the lexical entries themselves, what information should be considered so as to make it possible to record, as well as to capture characteristics as specific as those observed with the lexical units that make up the vocabularies of sign languages? To answer the proposed questions, a qualitative-descriptive and, at the same time, applied research was developed (TRIVIÑOS, 1990). The analyses were based on the assumptions of the General Theory of Lexicography, both as regards the construction of dictionaries of spoken languages (WIEGAND, 1984, 1989) and sign languages, more particularly (STOKOE, 1960, 1965, MCKEE & MCKEE, 2012); FELIPE and GP FENEIS, 2002; FELIPE and GP INES, 2005; CAPOVILLA; RAPHAEL, 2001; CAPOVILLA; RAPHAEL; MAURÍCIO, 2012; CAPOVILLA et al., 2017). The discussion took place in two parts: one more focused on the work of the lexicographer and its interaction with the lexical system (Front-end), as a way of giving theoretical support and applied to the proposed dictionary; and the other more focused on the formatting of lexical entries and guidelines for the end user. The following aspects, among others, are contemplated in this doctoral work: (i) the development of a taxonomic design, used as a basis for the implementation, already in use, of a monolingual electronic dictionary of Libras; (ii) discussion, definition and description regarding the criteria adopted for the composition of search keys; (iii) the details and explanations involved with the organization and structuring of lexical entries, both at the macro and microstructure levels.